Autophagy-Dependent Ferroptosis: Machinery and Regulation. Issue 4 (16th April 2020) - Liu, Jiao; Kuang, Feimei; Kroemer, Guido; Klionsky, Daniel J.; Kang, Rui; Tang, Daolin
Abstract : Macroautophagy (hereafter referred to as autophagy) is an evolutionarily conserved cellular process capable of degrading various biological molecules (e.g., protein, glycogen, lipids, DNA, and RNA) and organelles (e.g., mitochondria, endoplasmic reticulum [ER] ribosomes, lysosomes, and micronuclei) via the lysosomal pathway. Ferroptosis is a type of oxidative stress-dependent regulated cell death associated with iron accumulation and lipid peroxidation. The recently discovered role of autophagy, especially selective types of autophagy (e.g., ferritinophagy, lipophagy, clockophagy, and chaperone-mediated autophagy), in driving cells toward ferroptotic death motivated us to explore the functional interactions between metabolism, immunity, and cell death. Here, we describe types of selective autophagy and discuss the regulatory mechanisms and signaling pathways of autophagy-dependent ferroptosis. We also summarize chemical modulators that are currently available for triggering or blocking autophagy-dependent ferroptosis and that may be developed for therapeutic interventions in human diseases. Graphical Abstract: Abstract : Liu et al. describes types of selective autophagy and discuss the regulatory mechanisms and signaling pathways of autophagy-dependent ferroptosis. A deeper understanding of the process and function of autophagy-dependent cell death is critical for creating innovative therapeutic strategies for oxidative stress-related diseases.